2020
DOI: 10.1523/eneuro.0376-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

Differential Modulation of Ventral Tegmental Area Circuits by the Nociceptin/Orphanin FQ System

Abstract: The neuropeptide nociceptin/orphanin FQ (N/OFQ) can be released by stressors and is associated with disorders of emotion regulation and reward processing. N/OFQ and its receptor, NOP, are enriched in dopaminergic pathways, and intra-ventricular agonist delivery decreases dopamine levels in the dorsal striatum, nucleus accumbens (NAc), and ventral tegmental area (VTA). We used whole-cell electrophysiology in acute rat midbrain slices to investigate synaptic actions of N/OFQ. N/OFQ was primarily inhibitory, caus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 119 publications
1
14
0
Order By: Relevance
“…These effects are mediated by NOP receptors and appear to depend on enhancement of potassium conductance [ 66 , 67 ]. This conventional mechanism of action has been recently questioned in a study proposing the possibility that N/OFQ may attenuated DA transmission through indirect mechanisms involving presynaptic GABA transmission [ 68 ]. However, more conclusive experiments are needed to support this alternative hypothesis.…”
Section: Neurobiology Of the N/ofq-nop Receptor Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…These effects are mediated by NOP receptors and appear to depend on enhancement of potassium conductance [ 66 , 67 ]. This conventional mechanism of action has been recently questioned in a study proposing the possibility that N/OFQ may attenuated DA transmission through indirect mechanisms involving presynaptic GABA transmission [ 68 ]. However, more conclusive experiments are needed to support this alternative hypothesis.…”
Section: Neurobiology Of the N/ofq-nop Receptor Systemmentioning
confidence: 99%
“…At this level, N/OFQ treatment produced a decrease in tyrosine hydroxylase (TH) phosphorylation, DA synthesis and postsynaptic DA receptor D1 signaling [ 69 ]. On the other hand, in vivo microdialysis and ex vivo fast scan cyclic voltammetry studies revealed that N/OFQ application within the NAc has little or no basal effects on DA accumulation and release [ 68 , 70 ]. Altogether these data point to a predominant role of the VTA in mediating the effects of N/OFQ in DA release.…”
Section: Neurobiology Of the N/ofq-nop Receptor Systemmentioning
confidence: 99%
“…Wash in of JNJ-67953964 seemed to generate an inward current in a subset of neurons, and surprisingly this was observed more often at 10 nM than at 100 nM. We previously found that a small subset of VTA neurons respond to nociceptin/orphanin FQ with an inward current only at low concentrations, peaking at 10 nM [44], and CRF also increases VTA glutamatergic EPSCs at lower concentrations and inhibits them at higher concentrations [45], making such a pattern not entirely unprecedented. Together, these observations indicate potentially important, unanticipated properties of JNJ-67953964.…”
Section: Plos Onementioning
confidence: 89%
“…With regard to the cellular actions mediated by NOP activation by nociceptin/orphanin N/OFQ, they resemble those mediated by the other classes of opioid receptors, particularly the activation of K + conductances, the inhibition of high threshold voltage-gated Ca 2+ channels and the inhibition of transmitter release [121]. While most of VTA neurons responded with large outward currents to NOP activation [116], a recent study found that, NOP effects on the intrinsic membrane currents have different features depending on the projection areas of VTA and SNpc DA neuronal populations [117]. Medial-PFC and NAcc-projecting VTA neurons respond to NOP activation with an outward (inhibitory) membrane current; posterior anterior cingulate cortex (pACC)-projecting VTA neurons responded to NOP activation with an inward (excitatory) membrane current [117].…”
Section: Enkephalinergic Modulation Of Da Neuron Intrinsic Excitabilitymentioning
confidence: 98%